Agenda culinaria para 1896 de Blanco Prieto. Un estudio histórico del léxico de la gastronomía. - DALLE PEZZE, FRANCESCA; SARTOR, ELISA (Scripta)
The objective of this paper is two-fold: firstly, it aims at presenting Agenda culinaria para 1896. Libro de la compra. Con minutas y recetas para cada uno de los días del año, a book that displays editorial features that turn it into something more than a recipe book. As a matter of fact, it may be considered a consumer product that fits into the boom in publications related to cookery in the late 19th century. Secondly, it offers a study of the gastronomy lexicon that can be found in this volume, with the purpose of detecting foreign words, neologism and other lexical creations brought about by the contact between Spanish cuisine and ingredients and those from other countries and cultures. Therefore, this paper analyses the lexicographical trajectory of three terms (kari, uspot, pilaw) that offer a sample of the European and international circulation of lexicon of food and cookery, each one showing different paths and strategies of entry in the Spanish lexicon: double entry (kari), momentary loanwords (uspot), and predating (pilaw).